1993
DOI: 10.3168/jds.s0022-0302(93)77436-6
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Consistency as Related to Dietary Composition in Lactating Holstein Cows

Abstract: A trial was designed to study the relationships of dietary fiber and protein percentage and source to fecal consistency in lactating cattle. Thirty Holstein cows were assigned randomly to one of six TMR through four 21-d periods. The TMR were formulated to contain 17 or 25% ADF and CP of 15 or 22% with soybean meal supplementation or 22% with a combination of corn gluten and soybean meals. Two forage combinations were corn silage with or without alfalfa. Fecal consistency was evaluated using a four-point visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 14 publications
3
41
1
1
Order By: Relevance
“…There were no acidic samples with pH less than 6.5 in either normal or diarrheic cows. The fecal pH values in the present study were nearly the same as previous reports in dairy cows (pH 6.6–7.1; Ireland‐Perry & Stallings 1993). On average, higher lactate levels were observed in grazing cows.…”
Section: Discussionsupporting
confidence: 91%
“…There were no acidic samples with pH less than 6.5 in either normal or diarrheic cows. The fecal pH values in the present study were nearly the same as previous reports in dairy cows (pH 6.6–7.1; Ireland‐Perry & Stallings 1993). On average, higher lactate levels were observed in grazing cows.…”
Section: Discussionsupporting
confidence: 91%
“…Feces from cows fed BMR were drier (P < 0.03) than those from cows fed DP. Ireland-Perry and Stallings (1993) reported that dietary concentration of NDF was negatively correlated and concentration of dietary starch was positively correlated with fecal DM concentration, but neither of those 2 variables differed between hybrid treatments in this experiment. Excretion of fecal DM and water were not affected by MP, but fecal DM concentration was increased as MP increased.…”
Section: Manure Output and Digestibilitymentioning
confidence: 53%
“…Several articles published in extension magazines have described fecal scoring systems; however, due to a lack of sufficient peer reviewed scientific research; it was difficult to homogenize criteria to develop the scoring system used in the present study. The score was adapted from the study of Ireland-Perry and Stallings (1993) and was based on consistency, physical form and shape of the fecal material. In addition, the scoring system was validated by a preliminary pilot study, in which both authors of this article individually scored several fecal samples on the same farm until there was a consistent matching of scores with no more than a 0.5 point difference.…”
Section: Discussionmentioning
confidence: 99%